LGBT Representation In You Need To Calm Down-Taylor Swift Music Video - Fadeliyah Ikhwan; Muh. Akbar; Muliadi Mau (Metacommunication: Journal of Communication Studies, 2025)
Music videos have become a popular medium for conveying social messages. This study analyzes the representation of Lesbian, Gay, Bisexual, and Transgender (LGBT) messages in Taylor Swift's music video "You Need To Calm Down" using a semiotic approach. An in-depth analysis of the visual symbols, music, and lyrics in the video aims to reveal hidden meanings related to LGBT issues. The results of this study indicate the presence of visual codes that represent the LGBT community, such as the use of bright colors, eye-catching costumes, and scenes showing same-sex relationships, using John Fiske's semiotic analysis. This study makes a significant contribution to understanding how music videos can be used as a tool to campaign for social issues. The findings of this study can be a reference for other researchers who are interested in studying the representation of gender, sexuality, and identity in popular media.